PENGARUH EARNING PER SHARE, UKURAN PERUSAHAAN, DAN NET PROFIT MARGIN TERHADAP PRICE TO BOOK VALUE PADA PERUSAHAAN PERTAMBANGAN BATUBARA YANG TERDAFTAR DI BEI TAHUN 2012-2019 - bella pradita sari,; Muslihat, Asep (KRISNA: Kumpulan Riset Akuntansi, 2021)
The study entitled â€œthe effect of Earning Per Share, Firm Size, and Net Profit Margin against the Price to Book Value on the coal mining Companies registered in BEI 2012-2019â€. This type of research using a quantitative approach. The data used in this study is the annual financial report of the company coal mining sector registered in BEI 2012-2019. Data analysis used in this research is a multiple linear regression test. The results of the study found that earning per share has no effect on price to book value, firm size have an effect to price to book value, and net profit margin have an effect on price to book value.